Philosophy of Al-Farabi In Developing A Digital Music Notation Training Model for High School Art and Culture Teachers Based on CSCL - Handayani, Lucy; Masjhoedi, Soesanto; Lestari, Wahyu (LPPM Institut Seni Indonesia Padangpanjang, 2023)
This article explores the philosophical aspects of Al-Farabi in the development of a music art training model, aimed at assisting high school Art and Culture teachers in understanding and teaching digital music notation. Al-Farabi, a great philosopher from the Classical Islamic period, offers valuable insights into education and learning, which are applicable in the context of music art teaching. The article elucidates how Al-Farabi's views, particularly on ethics, morality, and happiness, can be integrated into a training model based on Computer Support Collaborative Learning (CSCL) to enrich the art teachers' learning experience. Furthermore, it provides an overview of how digital music notation can be implemented in high school cultural arts education and why this approach is relevant in the rapidly evolving context of music education. This article is expected to serve as a guide for developing a holistic and philosophical training model in music art education, focusing on understanding digital music notation and applying Al-Farabi's philosophical principles in the learning process. Additionally, this research highlights the importance of integrating technology in art education, demonstrating how digital approaches can broaden the horizons of music art learning. Moreover, the article seeks to prove how teaching methods inspired by Al-Farabi's thoughts can enhance students' creativity and conceptual understanding in music art.